2019
DOI: 10.1002/stem.3103
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells alleviate AQP-4-dependent glymphatic dysfunction and improve brain distribution of antisense oligonucleotides in BACHD mice

Abstract: Huntington's disease (HD) is a neurodegenerative disorder caused by a mutation in the huntingtin (HTT) gene that results in the production of neurotoxic mutant HTT (mHTT) protein. Suppressing HTT production with antisense oligonucleotides (ASOs) is a promising treatment strategy for HD; however, the difficulty of delivering ASOs to deep brain structures is a major barrier for its clinical application. The glymphatic system of astrocytes involving aquaporin 4 (AQP-4) controls the entry of macromolecules from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…While a proinflammatory role of AQP4 is consistent with the early study of Li et al [23], the present findings are not easily reconciled with recent studies suggesting that AQP4 may play an immunosuppressive role in models of MPTP and LPS induced neuroinflammation [62,63]. The latter studies reported that Aqp4 −/− mice treated with MPTP or LPS revealed an increased microglial inflammatory response and a more pronounced loss of TH-neurons in the SN, compared with WT mice.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…While a proinflammatory role of AQP4 is consistent with the early study of Li et al [23], the present findings are not easily reconciled with recent studies suggesting that AQP4 may play an immunosuppressive role in models of MPTP and LPS induced neuroinflammation [62,63]. The latter studies reported that Aqp4 −/− mice treated with MPTP or LPS revealed an increased microglial inflammatory response and a more pronounced loss of TH-neurons in the SN, compared with WT mice.…”
Section: Discussionsupporting
confidence: 59%
“…The list of neurological conditions in which AQP4 might play a pathophysiological role includes epilepsy [15,16] and neurodegenerative diseases, such as Alzheimer's disease (AD) [17][18][19][20], amyotrophic lateral sclerosis (ALS) [21,22], Huntington's disease (HD) [23] and spongiform encephalopathy (SE) [24]. Studies have also highlighted possible links between AQP4 and infectious and neuroinflammatory diseases, most notably meningitis [25], malaria [26] and neuromyelitis optica (NMO) [27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, targeting neurotoxic reactive A1 astrocytes may revise the neurodegeneration and repair the function of neurons in HD (22). Additionally, we found that reactive astrocytes impeded the delivery of antisense oligonucleotides (ASOs) to deeper brain structures whereas inhibition of reactive astrocytes could increase the efficacy of ASOs in transgenic HD animals (23). In clinical practice, disease burden calculated by CAP score, an index of cumulative toxicity of mHTT, is used to estimate the proximity to HD diagnosis and reflect the severity of striatal dysfunction (24,25).…”
Section: Discussionmentioning
confidence: 96%
“…For example, it has been shown that intrathecal administration of ASOs can reduce HTT levels by 70% in the cortex but only by 35% in the striatum. 54 Likewise, a bolus cisternal injection of ASOs reduces HTT levels by 60% in the cortex and by 36% in the striatum. 54 Another study also revealed that injection of ASOs into the CSF of non-human primates can reduce HTT mRNA levels by 53% in the anterior cortex but only 25% in the striatum.…”
Section: Discussionmentioning
confidence: 99%